Who uses green mobility? Exploring profiles in developed countries - Echeverría, Lucía (2022)
Mobility gives individuals access to different daily activities, facilities, and places, but at the cost of imposing environmental externalities. The sustainable growth of society is linked to green mobility (e.g., public transport, walking, cycling) as a way to alleviate individual carbon footprints. This study explores the socio-demographic profile of individuals performing green travel (public and active modes of transport) and identifies cross-country differences in green travel behavior. We rely on information from the Multinational Time Use Study, MTUS, for Bulgaria, Canada, Spain, France, Hungary, Italy, the Netherlands, the United Kingdom, and the United States, from 2000 to 2019. We estimate Ordinary Least Squares regressions modelling individual decisions regarding green mobility. Our results indicate that the socio-demographic and family profile of travelers is not homogenous across green modes of transport, with walking as a mode of travel exhibiting a much more consistent profile, across countries, in comparison to the use of public transport and cycling. Results indicate that some countries are more prone to green travel, and that transport infrastructure is a factor in the proportion of time spent on both public and active transport. Our findings help in understanding who is committed to green mobility, while revealing interesting systematic differences across countries.